Preschool Teachers and the Selection of Lyllabies in Activities with Preschool Children - Ljiljana S. Kostić (Inovacije u Nastavi, 2020)
Lullaby, as a literary form that is multifunctional for children - in terms of cognitive, emotional and social development, development of speech, perception and attention, stimulating curiosity and interest, and developing creativity - is an important element in achieving educational goals in the context of various aspects of child development. In this paper the authors examine the experience of preschool teachers (N = 302) with: (a) the selection of lullabies; (b) the selection of folk and artistic lullabies; (c) opting for vocal, instrumental, i.e., vocal-instrumental lullabies in their work with the youngest children, in order to understand the potential patterns of selection of this particular literary form and to contribute to the methodological education of the preschool teachers. The research results indicate that the selection of the lullabies is not particularly varied, and that preschool teachers more often opt for the authored lullabies, as well as for the titles that are available in a vocal-instrumental form. The empirical findings bring forth the problem of selecting the content for working with the youngest children, i.e., they open the question of the ability of the preschool teachers to mould the children’s literary taste, along with the question of the responsibility of methodologists, above all, the creators of educational policies, bearing in mind that according to the latest Preschool Education Program the choice of the content for activities with preschool children entirely rests upon preschool teachers.